Optimal speed control of SRM with integration of switching variable proportional desaturation fuzzy logic regulator for EV application - Kadali Ravi Kumar; Narender Jatoth; Shaik Mohammed Mukassir (Institute of Advanced Engineering and Science, 2026)
SRMs are recognized for their high efficiency, strong torque output, and capability to operate at high speeds, making them well-suited for electric vehicle (EV) applications. Their high initial torque effectively overcomes the vehicle's inertia during the drive mode, enhancing overall performance. Switched reluctance machines (SRMs) come in various structural configurations such as 8/6, 6/4, and 4/2, offering flexible options for different vehicle requirements. Speed control in SRMs is typically managed through current regulation, which is handled by a current controller. Traditionally, a proportional integral (PI) controller is used to generate the required reference current. However, the PI regulator is prone to high damping and sensitivity to disturbances, leading to increased speed overshoot during startup and longer settling times. To address these limitations, a switched variable proportional desaturation PI (SVPDPI) controller is employed. Nevertheless, due to its relatively slow response, the PI component in the SVPDPI is replaced with a fuzzy logic module to enhance controller performance. This results in a switched variable proportional desaturation fuzzy logic (SVPDFL) regulator, which significantly reduces initial speed overshoot and improves settling time toward the desired reference speed. This paper presents a comparative analysis of these controllers, with simulations conducted using MATLAB/Simulink to evaluate performance improvements.